Two Days in Ait Hadiddou: Traditions and Hosts in Moroccan High Atlas - Yassin Boudriq (Indonesian Journal of Tourism and Leisure, 2021)
Based on ethnographic observation of a festival organized in two villages in Moroccan High Atlas, this study analyzes the role of traditions and hosts in touristic areas. In this article, I gave a description of the festival in order to illustrate that traditions are not passive elements mobilized only to attract tourists. My ethnographic data shows that, firstly traditions can be mobilized against touristic event, in doing so, it statute changes from passive role, to active role by forcing a touristic event to change it activities. In the other hand, in my fieldwork, hosts are not just performers that try to attract tourists by performing and being confined by their traditions. In fact, they are active agents that innovate events and decide what to show to tourists. These tow results changes the perspective by which anthropologists approached the hosts/ guests interactions, and try to change the bias analysis that consider traditions as dependent always to tourism.